Estudo Eletroquímico de Catalisadores de Pt-Mo e Pt-Cd para a Oxidação Eletroquímica de Etileno Glicol para a possível Aplicação em Células a Combustível Diretas a Álcool - Coutinho, José William Diniz (2017)
The electrooxidation of ethylene glycol and its partial oxidation products was studied in platinum-containing electrocatalysts supported on high surface carbon Vulcan XC-72, molybdenum and cadmium (90:10, 80:20, 70:30) in medium acid. All catalysts prepared were synthesized by the alcohol reduction method with 20% metallic charge on the carbon substrate. X-ray diffraction (XRD) analysis showed that the bi-metallic catalysts of PtMo / C and PtCd / C presented cubic face-centered structures and no angular displacement was observed, making it impossible to identify the molybdenum in the catalyst And revealing the absence of alloying characteristics in these catalysts. Results of Transmission Electron Microscopy (MET) revealed that bi-metallic nanoparticles have sizes between 2.0 nm and 4.0 nm. The results of cyclic voltammetry, at room temperature, showed that the presence of Mo and Cd favor the initiation of oxidation at lower potentials than those observed for platinum. However, chronoamperometry data, at a constant potential of 0.50 V and ambient temperature, did not show significant variations in the catalytic current. On the other hand, with the increase in temperature from 25 ° C to 55 ° C, differences in current were observed, with the Pt90Mo10 electrode having the best results. Data obtained by High Performance Liquid Chromatography (HPLC) showed that Glycolide is the main by-product formed by the oxidation of ethylene glycol after electrolysis at 0.50 V.